The effect of banking deregulation on R&D investment: Evidence from the cross-regional operation of city banks - Peisen Liu; Shiqi Chen (Journal of Innovation & Knowledge (JIK), 2023)
Improving firms' innovation capability is crucial for promoting growth. In 2006 and 2009, China deregulated the banking industry and allowed city banks to set up branches across regions, which changed the banking structure and competition. Using data from financial licence information and 1,012,321 manufacturing firms in China during the 2004-2010 period, this study investigates the effects of banking deregulation on research and development (R&D) investment and provides a reference for firm innovation. The results show that city bank entry increases R&D investment by 0.084% and R&D investment increases by 0.037 percentage points with a 1% increase in cross-regional branches of city banks. The robustness and endogeneity tests confirm these findings. Mechanism tests reveal that city banks' deregulation encourages firms to participate in R&D activities and improve R&D investment by reducing financing constraints. The impacts of city banks' cross-regional operations on R&D investment are heterogeneous due to the variety in the geographical location, ownership, size, industry and age of firms. The promotion of banking deregulation on R&D investment comes from firms in the eastern region. The positive effect of banking deregulation is stronger for state-owned enterprises than private and foreign enterprises, stronger for large firms than small and medium firms, stronger for high-tech firms than ordinary firms and stronger for old firms than new firms. These findings provide evidence and implications for optimising financial structure to promote firm innovation and economic growth.
Keywords: G21; G28; G30; G32; 650; Banking deregulation; City banks; R&D investment; Financing constraints